How do financial reforms affect inequality through financial sector competition? Evidence from Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
In the first empirical study on how financial reforms have been instrumental in mitigating inequality through financial sector competition, we contribute at the same time to the macroeconomic literature on measuring financial development and respond to the growing field of economic development by means of informal sector promotion. Hitherto, unexplored financial sector concepts of formalization, semi-formalization and informalization are introduced. Four main findings are established: (1) while formal financial development decreases inequality, financial sector formalization increases it; (2) whereas semi-formal financial development increases inequality, the effect of financial semi-formalization is unclear; (3) both informal financial development and financial informalization have an income equalizing effect and; (4) non-formal financial development is pro-poor. Policy implications are discussed.
Keywords: E00; G20; I30; O17; O55; 330; Financial Development; Shadow Economy; Poverty; Inequality; Africa